2013
DOI: 10.1007/s00265-013-1521-x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in multiple modalities in male rhesus macaques: sex skin coloration and barks in relation to androgen levels, social status, and mating behavior

Abstract: The past decade has seen an increasing shift in animal communication towards more studies that incorporate aspects of signaling in multiple modalities. Although nonhuman primates are an excellent group for studying the extent to which different aspects of condition may be signaled in different modalities, and how such information may be integrated during mate choice, very few studies of primate species have incorporated such analyses. Here, we present data from free-ranging male rhesus macaques on sex skin col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 108 publications
3
60
2
Order By: Relevance
“…The authors interpret this evidence as evidence that red signals dominance in the macaques (Khan et al, 2011). However, this interpretation conflicts with the results of the observational studies described above, where red does not correlate with rank (Higham et al, 2013).…”
Section: Rhesus Macaquescontrasting
confidence: 56%
See 4 more Smart Citations
“…The authors interpret this evidence as evidence that red signals dominance in the macaques (Khan et al, 2011). However, this interpretation conflicts with the results of the observational studies described above, where red does not correlate with rank (Higham et al, 2013).…”
Section: Rhesus Macaquescontrasting
confidence: 56%
“…comm. in Vandenburgh, 1965), a recent study found no evidence that red coloration is linked to rank or to androgen levels during the mating season (Higham et al, 2013). No experimental studies have yet been published that examine male-male relationships in relation to red in rhesus macaques, although adult males do attend to female red coloration (Higham et al, 2011;Waitt et al, 2006).…”
Section: Rhesus Macaquesmentioning
confidence: 99%
See 3 more Smart Citations